Advanced Tertiary Lymphoid Tissues in Protocol Biopsies are Associated with Progressive Graft Dysfunction in Kidney Transplant Recipients - Lee, Yu Ho; Sato, Yuki; Saito, Mitsuru; Fukuma, Shingo; Saito, Masaya; Yamamoto, Shigenori; Komatsuda, Atsushi; Fujiyama, Nobuhiro; Satoh, Shigeru; Lee, Sang-Ho; Boor, Peter; Habuchi, Tomonori; et al. (Journal of the American Society of Nephrology, 2022)
Visual Abstract Significance Statement Tertiary lymphoid tissues (TLTs) are frequently found in transplanted kidneys, but their prevalence and clinical significance remain uncertain. Serial protocol kidney transplant biopsies without signs of rejection were collected and TLTs staged according to the presence of proliferating lymphocytes and follicular dendritic cells. TLTs rapidly developed within 1 month after kidney transplantation in approximately half of the 214 patients. Advanced TLTs, defined as the presence of follicular dendritic cells, were associated with progressive decline in graft function independent of interstitial inflammation score. These findings suggest advanced TLTs are strongly associated with late graft dysfunction, even in the absence of rejection. Background Tertiary lymphoid tissues (TLTs) are ectopic lymphoid tissues found in chronically inflamed organs. Although studies have documented TLT formation in transplanted kidneys, the clinical relevance of these TLTs remains controversial. We examined the effects of TLTs on future graft function using our histologic TLT maturity stages and the association between TLTs and Banff pathologic scores. We also analyzed the risk factors for the development of TLTs. Methods Serial protocol biopsy samples (0 hour, 1, 6, and 12 months) without rejection were retrospectively analyzed from 214 patients who underwent living donor kidney transplantation. TLTs were defined as lymphocyte aggregates with signs of proliferation and their stages were determined by the absence (stage I) or presence (stage II) of follicular dendritic cells. Results Only 4% of patients exhibited TLTs at the 0-hour biopsy. Prevalence increased to almost 50% at the 1-month biopsy, and then slightly further for 12 months. The proportion of advanced stage II TLTs increased gradually, reaching 19% at the 12-month biopsy. Presence of stage II TLTs was associated with higher risk of renal function decline after transplantation compared with patients with no TLT or stage I TLTs. Stage II TLTs were associated with more severe tubulitis and interstitial fibrosis/tubular atrophy at 12 months and predicted poorer graft function independently from the degree of interstitial inflammation. Pretransplantation rituximab treatment dramatically attenuated the development of stage II TLTs. Conclusions TLTs are commonly found in clinically stable transplanted kidneys. Advanced stage II TLTs are associated with progressive graft dysfunction, independent of interstitial inflammation.